Comparing content and input redirection in MDEs - Wallace, James; Mandryk, Regan; Inkpen, Kori (Conference on Computer supported cooperative work (CSCW 2008), 2008)
Designers of Multi-Display Environments (MDEs) often use input redirection to allow users to manipulate content on multiple displays with a single interaction device, but users seated at sub-optimal positions (i.e., not facing the display) may find interaction difficult or frustrating. In collaborative MDEs, users should be able to choose their preferred collaborative arrangement, rather than adjusting to the limitations of the technology. We compare content and input redirection from a variety of seating positions in an MDE. Results from our studies show that content redirection does not suffer from performance loss in sub-optimal seating positions, as opposed to input redirection, which does. Content redirection provides a method for all members of a group to interact with shared content regardless of their position relative to a shared display.